2020
DOI: 10.14295/cs.v11i.3313
|View full text |Cite
|
Sign up to set email alerts
|

Light quality on growth and phenolic compounds accumulation in Moringa oleifera L. grown in vitro

Abstract: All plant parts of the Moringa oleifera can contain relevant concentrations of phytochemicals with health benefits. Plants grown in vitro allow pathogen-free plant material production and rapid propagation, and this technique is widely used to obtain secondary metabolites. This study analyzed how light spectrum quality affects growth, chlorophyll, and total phenolic content in M. oleifera plants grown in vitro. M. oleifera seeds were inoculated in MS medium supplemented with 3% sucrose and 0.7% agar and were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
(41 reference statements)
0
2
0
1
Order By: Relevance
“…There are other known studies in which the production of phenolic compounds did not increase by stimulation with different lighting conditions. Da Silva et al (da Silva et al 2020) had tested the influence of red and blue LED light (70:30%) on the total phenolic content in Moringa oleifera shoots cultures. In vitro cultures grown under white light (control) accumulated more phenolic compounds than under the red and blue light (70:30%) conditions.…”
Section: The Total Flavonoid and Polyphenol Contentmentioning
confidence: 99%
“…There are other known studies in which the production of phenolic compounds did not increase by stimulation with different lighting conditions. Da Silva et al (da Silva et al 2020) had tested the influence of red and blue LED light (70:30%) on the total phenolic content in Moringa oleifera shoots cultures. In vitro cultures grown under white light (control) accumulated more phenolic compounds than under the red and blue light (70:30%) conditions.…”
Section: The Total Flavonoid and Polyphenol Contentmentioning
confidence: 99%
“…The polyphenols, flavonoids, MDA, and antioxidant capacity in moringa seed at 4 °C, 20 °C, and 30 °C showed that maximum phenolic compounds were observed at 20 °C and 30 °C [ 33 ]. da Silva et al [ 34 ] investigated the phenolic composition of different organs of Moringa oleifera , such as leaves, hypocotyls, and roots, and reported values ranging between 2.185 ± 0.089 mg GAE/g and 3.805 ± 0.304 mg GAE/g. Similar results were seen in faba beans, where polyphenolics were synthesized and accumulated at approximately the same time as seed priming throughout the germination process [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Os frutos verdes possuem todos os aminoácidos necessários à espécie humana e representam um alimento básico à população, além da espécie produzir compostos fenólicos e flavonoides, entre outros metabólitos secundários 4 , indicando seu potencial medicinal. De acordo revisão realizada por Silva et al (2020) 5 , a espécie possui uma série de atividades biológicas, com atividade anti-inflamatória, anticancerígena, antioxidante e antimicrobiana.…”
unclassified